Investigation of influence of elastic fillers on properties of elastomeric materials - Yu. A. Naumova; I. M. Agayants; V. G. Nikolsky; I. A. Krasotkina; O. E. Kochetova; A. S. Demakov; U. G. Zhirova (Тонкие химические технологии)
The article concerns an investigation of the influence of elastic fillers ratio - factice and the product of rubber recycling - on the properties of elastomeric materials based of binary polymer blend IR-BR.